Myth‐busting tropical grassy biome restoration. Issue 5 (6th September 2020) - Silveira, Fernando A. O.; Arruda, André J.; Bond, William; Durigan, Giselda; Fidelis, Alessandra; Kirkman, Kevin; Oliveira, Rafael S.; Overbeck, Gerhard E.; Sansevero, Jerônimo B. B; Siebert, Frances; Siebert, Stefan J.; Young, Truman P.; et al.
Abstract : The historical focus in research and policy on forest restoration and temperate ecosystems has created misunderstandings for the restoration of tropical and subtropical old‐growth grassy biomes (TGB). Such misconceptions have detrimental consequences for biodiversity, ecosystem services, and human livelihoods in woodlands, savannas, and grasslands worldwide. Here, we demystify TGB restoration myths to promote a positive agenda to increase the likelihood of success of ambitious landscape‐scale restoration goals of nonforest ecosystems. The 10 TGB restoration myths are: (1) grasslands originate from degraded forests, (2) tree cover is a reliable indicator of habitat quality, (3) planting trees is always good for biodiversity and ecosystem services, (4) grasslands are biodiversity‐poor and provide few ecosystem services, (5) enhancing plant nutrition is needed in restoration, (6) disturbance is detrimental, (7) techniques used to restore temperate grasslands also work for TGB, (8) grasslands represent early stages of forest succession, (9) grassland restoration is only about grasses, and (10) grassland restoration is fast. By demystifying TGB restoration, we hope that policymakers, scientists, and restorationists come to understand and embrace the value of these ecosystems and are motivated to establish policies, standards, indicators, and techniques that enhance the success of TGB restoration. We must abandon misperceptions and misunderstandings of TGB ecology that result in ill‐conceived policies and build an informed and compelling global ecosystem restoration agenda that maintains and improves the well‐being of all inhabitants of grassy biomes.